2019
DOI: 10.1097/sla.0000000000002722
|View full text |Cite
|
Sign up to set email alerts
|

Increased Rate of Long-term Mortality Among Burn Survivors

Abstract: Burn survivors have a significantly higher rate of long-term mortality than matched controls, particularly related to trauma and mental illness. Burn follow-up should be focused on injury prevention, mental healthcare, and detection and treatment of new disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…(22) Similar to sepsis and trauma, burn survivors have a greater long-term mortality than matched controls, as well as increased mental illness. (23, 24) CCI has been demonstrated after severe acute pancreatitis as well. Yang et al determined that individuals with severe acute pancreatitis with prolonged durations of stay in the ICU had greater morbidity and rates of PICS, which was a risk factor for post-ICU mortality and poor quality of life in these patients.…”
Section: Long-term Outcomes Of CCI and Picsmentioning
confidence: 95%
“…(22) Similar to sepsis and trauma, burn survivors have a greater long-term mortality than matched controls, as well as increased mental illness. (23, 24) CCI has been demonstrated after severe acute pancreatitis as well. Yang et al determined that individuals with severe acute pancreatitis with prolonged durations of stay in the ICU had greater morbidity and rates of PICS, which was a risk factor for post-ICU mortality and poor quality of life in these patients.…”
Section: Long-term Outcomes Of CCI and Picsmentioning
confidence: 95%
“…Burn injuries cause severe damage to the epidermis, dermis, and underlying tissue, often resulting in physical and mental illnesses [ 1 ]. Ideally, burn wound dressings should be infection-resistant, retain moisture, and facilitate tissue regeneration [ 2 ].…”
Section: Introductionsmentioning
confidence: 99%
“…Two population-based cohort studies followed burn patients for many years after hospital discharge and revealed increased all-cause mortality compared to matched controls. One study had age limit >45 years and no TBSA limit while the other study had a TBSA limit >10% (34,35). Moreover, younger age and good pre-existing medical A c c e p t e d M a n u s c r i p t condition are associated with long-term survival after burn injury (36).…”
Section: Mortality During Follow-upmentioning
confidence: 99%